KONFLIK TOKOH UTAMA DALAM NOVEL TANAH SURGA MERAH KARYA ARAFAT NUR - Alzuardi, Rikki; Priyadi, Antonius Totok; Muzammil, Ahmad Rabiâ€™ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractA common problem in this study is "How do the main characters conflict in the novel Tanah Surga Merah by Arafat Nur? The general problem is divided into two subproblems, namely the internal conflict of the main character and the external conflict of the main character in the novel Tanah Surga Merah by Arafat Nur. The purpose of this study is to describe these two subproblems, while this research is useful for researchers to increase knowledge and understanding in analyzing literary works, can also be used by teachers and students as learning media and research material for other research.The theory used in this research is about novels, characters, characterization and conflict. This research uses descriptive analysis, qualitative research, and psychological research. The source of the research data is the novel Tanah Surga Merah by Arafat Nur. The data collection technique in this research is the documentary study technique. The data in this study are quotations cited by the main character conflict in the novel Tanah Surga Merah by Arafat Nur. Based on the results of data analysis, it can be concluded that: 1) There are 10 types of internal conflicts in the novel Tanah Surga Merah by Arafat Nur namely; confused, sad, uncertain, scared, happy, relieved, suspicious, hurt, embarrassed, disappointed. 2) There are 2 external conflicts in the novel Tanah Surga Merah by Arafat Nur namely; physical conflict and social conflict.The results of this study can be implemented in Indonesian language learning in high school students in class XII semester II. The author hopes that this research can be continued by further researchers to discuss in terms of other problems.Â Keywords: conflict, main character, psychology, novel